Acquiring new complex endoscopic skills: experience from the development of peroral endoscopic myotomy (POEM) in Malaysia - Ho, Shiaw Hooi; Nik Muhamad Affendi, Nik Arsyad; Lau, Peng Choong; Jamaludin, Fadhil; Mahadeva, Sanjiv (John Wiley and Sons Inc., 2021)
Peroral endoscopic myotomy (POEM) has rapidly gained popularity as an effective treatment modality for achalasia. However, POEM services in the South East Asian region are not widely available due to either a lack of expertise or interest. In this article, we describe how a POEM service can be developed through a combination of networking with regional experts, having prior experience of endoscopic submucosal dissection (ESD), attending animal model workshops, collaborating with upper gastrointestinal surgeons, and working together in a multidisciplinary team. A total of 68 POEM procedures have been performed since 2015, with a 94.1% technical and 93.4% clinical success rate, and a 21.5% minor complication rate. We believe that our model may be useful for other Endoscopy Units in the region, which are performing advanced therapeutic endoscopy, to develop a POEM service too.